Wdrożenie metody konsultacji edukacyjnych w szkołach arabskich w Izraelu z perspektywy nauczycieli - Ramadan, S. Izabel (Studia Edukacyjne, 2020)
The role of the educational counsellor in schools has undergone modification in response to recent changes in social, familial and pupil characteristics. The traditional, one-on-one approach has gradually been replaced with collaborative methods that are more in keeping with the times, more comprehensive and more proactive. One method of collaborative teaming that has increasingly found its way into schools is consultation. This is an indirect intervention process based on interaction between counsellors (“consultants”) and teachers (“consultees”) where the former provide professional advice, within their fields of specialization, for dealing with specific problems encountered by teachers in their day-to-day work. It is meant to support teachers in dealing with the demanding school environment by primarily working directly with them rather than with pupils and by providing important professional resources and problem-solving skills. My research examined this method from the perspective of teachers in Israeli schools in Nazareth, where the student population and the teachers are Arab. Data were collected using in-depth interviews. Among other things, the results indicated a willingness on the part of teachers to adjust to new methods but pointed to systemic obstacles to effective implementation.